AN ANALYSIS OF ENGLISH TEACHERS STRATEGIES IN IMPROVING STUDENTS READING SKILLS IN A PRIVATE ELEMENTARY SCHOOL OF NGABANG - Yuyun, Nurpiani; Upa, Yunika (JOEEL (Journal of English Education and Literature), 2025)
Reading skills are crucial for elementary school students, especially in English learning. Students can understand the text if they have good reading skills. Therefore, teachers should provide appropriate strategies to improve students' reading skills. The purpose of this study was to find out what strategies English teachers used in improving students' reading skills in a private elementary school in Ngabang. This research used a descriptive qualitative method. This research was conducted at SDS Alfa Omega Ngabang. The subjects in this study were two English teachers who taught in class 5. The data collection instruments in this study used observation and interview. Data analysis used data reduction, data display, and conclusion drawing and verification. The results showed that there were five strategies used by English teachers: previewing text, guessing word meaning, skimming, scanning, and reading aloud. The reading aloud strategy is the most frequently used strategy by teachers at SDS Alfa Omega Ngabang because teachers feel that this strategy can train students' pronunciation, make students active, and increase students' motivation and interest in reading. It is suggested that teachers can choose strategies for teaching reading skills based on the students' ability level and education level.